PATRIOTISM IN CHILDREN’S LITERATURES OF THAILAND AND SINGAPORE - Yadi, Supawadi; Thi Hang, Truong; Raktham , Chutigarn; Wittayasakpan, Sompong (Journal of Buddhist Anthropology, 2021)
The objectives of this article were to study the patriotic ideals of Thai and Singaporean children’s literature. There were 55 stories have been used in this study and categorized into 40 Thai children’s literature awarded by Office of the Basic Education Commission (OBEC) and 15 highly acclaimed Singaporean children’s literature. A textual analysis of children’s literature works was utilized as a tool for data collection and described in analytical manner. From this study, it can be found that the content can be classified into 2 categories of children’s literature: category 1 is a group that expresses the media content of 14 implicit patriotic ideologies, and category 2 is a group that shows content in the media showing the ideology of patriotism and connotation of 41 stories. In this regard, Thai children’s literature presents an ideology of patriotism, both direct and implicit, such as nation, religion, and monarchy, while Singaporean children’s literature presents a patriotic ideology, namely leader, leadership qualities, ethnic diversity and family. Instilling a sense of patriotism as found on Thai children’s literature will shape cognition for children and juvenile, creating a good harmonious sense to happily live in the same country, while in Singaporean literature, it presents a benefit of good international relations, global affairs related to human activities, racial diversity and recognition of racial differences under the same country in peaceful manner. Similarity of Thai and Singaporean is peacekeeping and harmonious mindsets under the differences and cultural diversities, while the dissimilarity is Thai literature presenting the application of Buddhism as a guidance in the way of life; on the other hands, this is not the case in Singaporean literature.